Analisis Faktor-Faktor Yang Mempengaruhi Minat Pemuda Untuk Berusaha Di Sektor Pertanian Desa Prambatan Kecamatan Balen Kabupaten Bojonegoro - Hardina, Tri; Tri Wahyu Nugroho; Hery Toiba; Nuhfil hanani; Suhartini (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
This research aims to find out how young people are interested in starting a business in the agricultural sector and what factors influence young people's interest as well as formulating a strategy to increase young people's interest in starting a business in the agricultural sector in Prangkat Village, Balen District, Bojonegoro Regency. This research was conducted using qualitative and quantitative methods and data collection using interview methods, documentation and the help of questionnaires. The research sample consisted of 90 respondents and were young people with age criteria of 15-25 years, using random sampling techniques, and the analysis model used probit regression. The results of research on youth interest in starting a business in the agricultural sector in Prangkat Village, Balen District, Bojonegoro Regency are in the medium category. Interest in working in the agricultural sector is influenced by factors such as age, gender, marital status, education, parents' occupation, parents' income, land area, experience, and social media ownership. The driving factor for young people's interest in working in the agricultural sector is the experience they have in the agricultural sector.